The Fentanyl System Shock - Are There Lessons to Learn From the COVID-19 System Shock Framework?; Comment on "The COVID-19 System Shock Framework: Capturing Health System Innovation During the COVID-19 Pandemic" - Maximilian Meyer; Jean N. Westenberg; R. Michael Krausz (Kerman University of Medical Sciences, 2023)
The Sydney Children's Hospitals Network (SCHN) addressed the challenges of the COVID-19 pandemic by implementing innovative changes which made their health system resilient and responsive. For other healthcare systems, there are important takeaways. In the United States and Canada, an urgent widespread response is needed to address the overdose crisis, driven by potent synthetic opioids (ie, fentanyl and its derivates). We project the COVID-19 System Shock Framework (CSSF) on to the North American healthcare systems and suggest a Fentanyl System Shock Framework, which provides a framework for necessary changes and innovations to address the overdose crisis. To become resilient to the fentanyl system shock, core components as well as overarching values, health policy, and online technologies need to be adapted to reduce the death count and meet the evolving needs of marginalised individuals who use opioid. Future research should focus on scientifically assessing such implementations to guide evidence-based decision making.